2021
DOI: 10.1055/s-0041-1735193
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel versus Ticagrelor in CYP2C19 Loss-of-Function Allele Noncarriers: A Real-World Study in China

Abstract: Objective This article compares the clinical outcomes of clopidogrel and ticagrelor in patients with acute coronary syndrome (ACS) without cytochrome P450 (CYP)2C19 loss-of-function (LOF) alleles and investigates whether clopidogrel could be an alternative P2Y12 inhibitor without increasing the risk of ischemic events. Methods Patients were divided into the clopidogrel-treated group and the ticagrelor-treated group. Inverse probability of treatment weighting (IPTW) calculated by propensity scores was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…This reason might be that younger patients had a lower risk of bleeding, and clinicians preferred to select the stronger P2Y12 inhibitor. The mean age of the ACS patients in the study was about 60 years, which seemed to be younger than Caucasian populations, but it was similar to that of ACS patients from the previous studies in China ( 22 24 ). The main reasons include: (1) China a developing country, many patients do not receive sufficient medical care, such as follow-up visits by family doctors, careful monitoring of blood glucose and blood pressure; (2) Many patients in China are heavy manual workers, which is also an important risk factor for ischemic heart disease ( 25 ).…”
Section: Discussionsupporting
confidence: 76%
“…This reason might be that younger patients had a lower risk of bleeding, and clinicians preferred to select the stronger P2Y12 inhibitor. The mean age of the ACS patients in the study was about 60 years, which seemed to be younger than Caucasian populations, but it was similar to that of ACS patients from the previous studies in China ( 22 24 ). The main reasons include: (1) China a developing country, many patients do not receive sufficient medical care, such as follow-up visits by family doctors, careful monitoring of blood glucose and blood pressure; (2) Many patients in China are heavy manual workers, which is also an important risk factor for ischemic heart disease ( 25 ).…”
Section: Discussionsupporting
confidence: 76%
“…The reason might be that Chinese clinicians were more willing to prescribe clopidogrel than ticagrelor compared with European and American countries. 45,46 Therefore, adjustment of P2Y12 receptor inhibitors based on PFT, especially the upgrading of P2Y12 receptor inhibitors, might have more clinical benefits for Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Standardized differences of ≤ 0.10 indicated well-balanced covariates while using IPTW. Covariates used in these two models were selected based on the previous studies and were reported to be related to clinical outcomes ( 16 18 ). The final models included age, sex, body mass index (BMI), smoking status, PCI indication, PCI type, stent number, multiple-vessel disease, medical history (previous PCI with stenting, previous coronary artery bypass grafting, hypertension, hyperlipidemia, diabetes mellitus, MI, heart failure, and cerebral infarction), left ventricular ejection fraction, estimated glomerular filtration rate, and discharge medication (statin, angiotensin-converting enzyme inhibitor or angiotensin receptor blocker, beta blocker, and proton pump inhibitor).…”
Section: Methodsmentioning
confidence: 99%